Humidified High Flow Nasal Cannula (HHFNC) Therapy in Critically Ill Children: Nation-Wide Survey - Saira Abrar, Shaikh Ali Masood, Anwarul Haq, Heera Nand Rathore, Syed Qutub Jamal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the experience regarding current practices of HHFNC in terms of techniques uses, indications and complications among severely ill children. Material and methods: This prospective online survey was conducted to examine current HHFNC practice in neonatal and paediatric intensive care units of the Pakistan. There was no agreement in this survey on how to define HFNC in paediatric patients or how to establish or alter flow. An online questionnaire was used for data collection to assess the current HHFNC practice in Pakistan. The survey questionnaire was based on information regarding the hospital, HHFNC use, indications, and the consequences. Furthermore, questions were raised about individual practice and whether or not HHFNC had been established as a safe therapeutic intervention. If a respondent, such as a physician, nurse or the resident had used HHFNC before, additional questions have been asked concerning the indications for usage and the weaning procedure. Statistical analysis was performed using SPSS version 26. Results: The response was received from 204 physicians and nurses. Majority of responders 85% has experienced to used HFNC. 63% of the responders have been using HFNC for more than 3 years. Acute respiratory failure was considered a good indication for HFNC by all 193(95%). Many Physicians used HFNC initiation and weaning protocol. According to the complications the abdominal distension was experienced by 9.8% preteritions, followed by nasal mucosal by 29.4%, irritability 19.16% and Pneumothorax/Barotrauma experienced by 22.5% of the pediatricians, while sedation have experienced while on HFNC by the 15.2% of the participants. According to respondent’s experience the 89% of the parents were satisfied with the use of HFNC and 98.5% of physicians recommended to other colleagues. Conclusions: As per study conclusion this survey presented the first national assessment of the increasing usage of HFNC as a source of oxygen for children, with HFNC being largely acknowledged as a noninvasive and safe technique. There were a variety of indicators. This was the first national review of HFNC’s expanding usage in paediatric critical care.